2003
DOI: 10.1029/2003tc001524
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic deformation linking the east Anatolian and Karataş‐Osmaniye intracontinental transform fault zones in the Gulf of İskenderun, southern Turkey, deduced from paleomagnetic study of the Ceyhan‐Osmaniye volcanics

Abstract: Left‐lateral strike slip along the Dead Sea Fault Zone (DSFZ) between the African and Arabian plates is partitioned into a complex set of motions at its northern extension where Arabia impinges into the Anatolian collage. As a result, the nature of the contemporary link between the east Anatolian and Dead Sea transforms is unclear. To quantify strike slip motion expressed as tectonic rotations along the inferred southwest continuation of the East Anatolian Fault Zone (EAFZ), we have investigated the paleomagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…Arger et al (2000) and was shown by Gürsoy et al (2003) to be reverse-magnetised, so its probable age is ~800 ka, late in the Matuyama chron. Seyrek et al (2008) and offsetting the NE margin of the outcrop by ~400 m along a bluff indicative of downthrow to the SE by ~50 m. In-situ basalt is evident on the NW side of this fault (c. YF 64169 89705) and on its SE side (c. YF 64576 89986), at points that are ~500 m apart, but the area in between has been obliterated to build a motorway to serve the port, so it is hard to say whether this is a true leftlateral offset.…”
Section: Active Faulting To the Southwest Of Osmaniyementioning
confidence: 99%
“…Arger et al (2000) and was shown by Gürsoy et al (2003) to be reverse-magnetised, so its probable age is ~800 ka, late in the Matuyama chron. Seyrek et al (2008) and offsetting the NE margin of the outcrop by ~400 m along a bluff indicative of downthrow to the SE by ~50 m. In-situ basalt is evident on the NW side of this fault (c. YF 64169 89705) and on its SE side (c. YF 64576 89986), at points that are ~500 m apart, but the area in between has been obliterated to build a motorway to serve the port, so it is hard to say whether this is a true leftlateral offset.…”
Section: Active Faulting To the Southwest Of Osmaniyementioning
confidence: 99%
“…Farther SW, the Botaş basalt (11 in Fig. 3) was K-Ar dated by Arger et al (2000) to 630 ± 180 ka (± 2σ) and was shown by Gürsoy et al (2003) to be reversemagnetised. An age for it late in the Matuyama chron (∼800 ka) can thus be deduced.…”
Section: Active Crustal Deformationmentioning
confidence: 96%
“…The subsequent realisation by Westaway (2003Westaway ( , 2004 that the northern DSFZ is strongly transpressive eliminates any geometrical requirement for active leftlateral slip along the line of the KOFZ or Düziçi Fault, contrary to what had been deduced previously, based on the assumption that the active left-lateral faults in this region are all transform faults. The argument by Gürsoy et al (2003) that the KOFZ must be active to account for vertical-axis rotations measured palaeomagnetically in the Ceyhan-Osmaniye basalts is not compelling, as these measurements can readily be explained differently (see the online supplement). In other recent interpretations, such as that by Robertson et al (2004), and in some older schemes (e.g., Kelling et al, 1987), the KOFZ is regarded as a reverse-fault zone associated with the development of the mid-Cenozoic subductionaccretion complex; its along-strike continuation north and east of Osmaniye thus trends SSW-NNE along the Neotethys suture, not SW-NE across the Amanos Mountains (Fig.…”
Section: Active Crustal Deformationmentioning
confidence: 96%
See 1 more Smart Citation
“…The differential character of this deformation is now well established by regional palaeomagnetic studies (Gürsoy et al, 1997(Gürsoy et al, , 1998(Gürsoy et al, , 2003Tatar et al, 2002;Piper et al, 2006Piper et al, , 2010. These show that block rotations produced by high strains north of the indenter are strongly counter clockwise (CCW) but become relatively less CCW as the strain diminishes to the west of the indenter, so that rotations diminish to near-zero in central Anatolia; still further to the west they become progressively more clockwise (CW) near the western extremity of the extruded terranes.…”
Section: Introductionmentioning
confidence: 92%